Analisis Kinerja Pengering Surya Tipe Rak Menggunakan Heat Absorber Pelat Gelombang dengan Aliran Udara Natural - Jamal Jamal (Politeknik Negeri Ujung Pandang, 2022)
The current study aims to determine the performance of a rack-type solar dryer. The solar dryer uses a heat absorber in the form of a large wave plate and a small wave which is placed in the solar collector room. The dried material is cassava. The system used is natural air flow due to density differences. The research was carried out by making two rack-type solar collectors, the difference being the heat absorber used, one large wave and the other small wave. The test was carried out simultaneously between the two solar dryers. In this study, the results of large-wave solar dryers with an average efficiency of 9.24% had a better performance than small-wave solar dryers with an average efficiency of 7.68%. In the large wave solar dryer, the average efficiency on rack 1 is 1.33%, on rack 2 is 3.83% and on rack 3 is 5.93%. In the small wave solar dryer, the average efficiency on rack 1 is 1.50%, on rack 2 is 3.88% and on rack 3 is 2.30%.